Template Assisted Synthesis of Molecularly Imprinted Polymer for the Extraction of p-Coumaric Acid - Ahmad Bhawani, Showkat; Binti Suhaili, Nursuhailah; Marcella Roland, Rachel; Bakhtiar, Salma; M. Alotaibi, Khalid; Nasir Mohammad Ibrahim, Mohammad (Asian Journal of Chemistry, 2020)
In present study, the molecular imprinting polymer (MIP) of p-coumaric acid was synthesized by using p-coumaric acid as a template, acetonitrile as solvent, 1,4-butanediol dimethacrylate as cross-linker, acrylic acid as monomer and 2,2-azobisisobutironitrile (AIBN) as the initiator. The synthesized polymers were characterized by FTIR and SEM. The results from SEM revealed that the polymer was in spherical shape with size in micro-range. The binding efficiency of polymers was analyzed by adsorption study. The highest rebinding efficiency for MIP was 80% while for non-imprinted polymer (NIP) it was only 24%.